The Analysis of the Gear Profile of A Rolling-Friction Cycloid Speed Reducer - Lin Jing; et al. (Jixie chuandong)
The rolling-friction cycloid speed reducer has two kinds of tooth profiles─a hypocycloid and an epicycloid. Although their characteristics are diffenent, they both have same overcutting problem. By theoretical analysis, a conclusion that the speed reducer can’t be overcutting if its epicycloid gear pnofile is not overcutting is gained.